Visualizing Lipid Raft Dynamics and Early Signaling Events during Antigen Receptor-mediated B-Lymphocyte Activation - Gupta, Neetu (The American Society for Cell Biology, 2003)
Recent biochemical evidence indicates that an early event in signal transduction by the B-cell antigen receptor (BCR) is its translocation to specialized membrane subdomains known as lipid rafts. We have taken a microscopic approach to image lipid rafts and early events associated with BCR signal transduction. Lipid rafts were visualized on primary splenic B lymphocytes from wild-type or anti-hen egg lysozyme BCR transgenic mice, and on a mature mouse B-cell line Bal 17 by using fluorescent conjugates of cholera toxin B subunit or a Lyn-based chimeric protein, which targets green fluorescent protein to the lipid raft compartment. Time-lapse imaging of B cells stimulated via the BCR with the antigen hen egg lysozyme, or surrogate for antigen anti-IgM, demonstrated that lipid rafts are highly dynamic entities, which move laterally on the surface of these cells and coalesce into large regions. These regions of aggregated lipid rafts colocalized with the BCR and tyrosine-phosphorylated proteins. Microscopic imaging of live B cells also revealed an inducible colocalization of lipid rafts with the tyrosine kinase Syk and the receptor tyrosine phosphatase CD45. These two proteins play indispensable roles in BCR-mediated signaling but are not detectable in biochemically purified lipid raft fractions. Strikingly, BCR stimulation also induced the formation of long, thread-like filopodial projections, similar to previously described structures called cytonemes. These B-cell cytonemes are rich in lipid rafts and actin filaments, suggesting that they might play a role in long-range communication and/or transportation of signaling molecules during an immune response. These results provide a window into the morphological and molecular organization of the B-cell membrane during the early phase of BCR signaling.